Stent with super-lubricating coating as well as preparation method and application of stent
By modifying the surface of the stent, a superlubricated coating composed of a substrate pretreatment layer, a superhydrophobic layer and a lubricating layer is constructed, which solves the problem of the existing stent being prone to infection and reobstruction after implantation, and improves the durability and biocompatibility of the stent, and reduces the risk of adverse reactions.
Patent Information
- Application Number
- CN202411850040.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-25
AI Technical Summary
Existing stents are prone to complications such as infection and reobstruction after implantation, and due to the complex body fluid composition, the functional surface is damaged in a short period of time, making it difficult to maintain effectiveness.
The scaffold surface is modified using FDA-certified biocompatible materials to construct a superlubricated coating composed of a substrate pretreatment layer, a superhydrophobic layer and a lubricating layer. The coating forms a rough porous surface by ionization or nanoparticle loading, followed by spraying or dipping using a fluorinated carbon material and a fluorinated lubricating liquid to form a stable superhydrophobic and lubricating layer.
It significantly improves the durability and biocompatibility of the stent, effectively reduces the risk of adverse reactions such as infection, thrombosis and restenosis that may occur after implantation, and maintains long-term anti-fouling performance.
Smart Images

Figure CN119868667A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and in particular relates to a stent with a super-lubricating coating, a preparation method and use thereof. Background Art
[0002] Lumen stenosis is a common clinical disease with a variety of causes, such as stones, inflammation, and tumors. Lumen stenosis causes the inability to excrete fluids in the physiological environment normally, resulting in a series of complications that seriously endanger the patient's life safety. At present, the main clinical treatment for stenosis is to place stents through endoscopy to open the narrow lumen and maintain normal fluid excretion. However, in clinical practice, after stent implantation, the stent will provide adhesion sites for bacteria and biofilms, which will not only increase the incidence of infectious diseases in the early stage of stent implantation, but also, as the stent implantation time increases, various components in body fluids such as bile and urine will adhere to the stent surface and form stones on the stent, greatly reducing the therapeutic effect after stent implantation. Therefore, it is of great clinical significance to modify the surface of conventional stents to reduce the incidence of stent-related stones and stent-related infections.
[0003] At present, some studies have modified the surface of the stent to regulate the physical and chemical properties of the stent surface, thereby reducing the incidence of stent-related calculi and other complications. Some studies have reduced the incidence of stent-related calculi by coating a layer of hydrophilic polymer material on the surface of the stent, using the hydrophilic coating to form a water film on the surface of the material to reduce the adhesion of body fluid components. In addition, some studies have explored the use of nanotechnology to modify the surface of the stent. For example, the introduction of nanostructures or nanomaterials on the surface of the stent can increase the hydrophobicity and antibacterial properties of the stent surface, thereby reducing the adhesion of surface substances and the occurrence of infection. These studies have provided new ideas and methods for reducing the incidence of stent-related stones and infections. However, in clinical practice, most stents, such as biliary and urethral stents, have relatively complex body fluid components, and the above-mentioned functional surfaces will be destroyed in a short time, and the ideal effect cannot be achieved.
[0004] In view of the many problems currently faced by clinical stents, such as complications such as infection and restenosis after implantation, this invention has made innovative improvements. We use FDA-approved biocompatible materials and perform fine modification and optimization design on the stent surface. This improvement not only significantly improves the durability and biocompatibility of the stent, but also effectively reduces the risk of adverse reactions such as infection, thrombosis and restenosis that may occur after implantation. Summary of the invention
[0005] One object of the present invention is to provide a stent with a superlubricating coating, and a second object of the present invention is to provide a method for preparing a stent with a superlubricating coating.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] In a first aspect, the present invention provides a stent with a super-lubricating coating, characterized in that the stent is composed of a stent substrate and a super-lubricating coating, and the super-lubricating coating is composed of a substrate pretreatment layer, a super-hydrophobic layer and a lubricating layer on the inside and outside.
[0008] The super hydrophobic layer material is selected from fluorinated carbon materials, such as perfluorooctyltrichlorosilane, perfluorodecyltriethoxysilane, perfluorodecyltrichlorosilane, nonafluorohexyltrimethoxysilane, and tridecafluorooctyltrimethoxysilane, or a combination of two or more thereof; the lubricating layer material is selected from fluorinated lubricants such as perfluorodecalin, fluorinated polyether, and fluorinated alkane amine.
[0009] The stent described in the present invention is a supporting material or a prosthesis for expanding a body cavity, wherein the body cavity includes at least one of a blood vessel, an esophagus, a bile duct, a trachea, a bronchus, a small intestine, a large intestine, a urethra or a ureter.
[0010] The stent of the present invention includes a metal stent or a plastic stent.
[0011] In some embodiments of the present invention, the stent substrate of the metal stent is selected from at least one of nickel-titanium alloy, cobalt-chromium alloy, magnesium alloy, stainless steel, tantalum alloy and titanium alloy.
[0012] In some embodiments of the present invention, the support substrate of the plastic support is selected from at least one of polyethylene (PE), polyurethane (PU), polytetrafluoroethylene (PTFE), polypropylene (PP), polyvinylidene fluoride (PVDF), polyetheretherketone (PEEK), polylactic acid (PLA), and polycaprolactone (PCL).
[0013] The substrate pretreatment layer is based on the stent substrate, and the stent substrate is pretreated by ionization or nanoparticle loading to prepare a rough porous surface. The rough porous surface has a high specific surface area, which is conducive to the adhesion of the fluorinated carbon material of the super hydrophobic layer and the fluorinated lubricating liquid of the lubricating layer. The super hydrophobic layer composed of the fluorinated carbon material and the lubricating layer composed of the fluorinated lubricating liquid are prepared by conventional methods, including but not limited to spraying and dipping.
[0014] When the bracket is a metal bracket, the substrate pretreatment layer is prepared by the following method: using the metal bracket as an anode and a graphite electrode as a cathode, selecting corresponding electrolyte and voltage according to the material properties to anodize the surface of the metal bracket to prepare a porous anodized surface.
[0015] In a specific embodiment of the present invention, the metal stent is a nickel-titanium alloy metal stent, and the electrolyte is a glycerol ammonium fluoride solution with a volume fraction of 0.5-1.0%.
[0016] In a specific embodiment of the present invention, the substrate pretreatment layer of the nickel-titanium alloy metal stent is prepared by the following method: the nickel-titanium alloy metal stent is used as an anode, the graphite electrode is used as a cathode, and a 0.5% volume fraction of propylene glycol ammonium fluoride solution is used as an electrolyte. Anodization is performed for 6-24 hours under 30V, 300mA DC power supply conditions, and the oxidized anode is heat-treated with a peak temperature of 400°C for 6-12 hours and an annealing time of 30 minutes to obtain a porous anodized surface. The porous anodized surface obtained in the specific embodiment of the present invention is as follows Figure 1 As shown, Figure 1 The left (NiTi alloy) is a non-ionized metal surface. Figure 1 The right side (anodized) shows the metal surface after ionization. It can be seen that ionization causes multiple holes to appear on the surface of the nickel-titanium alloy, forming a rough surface.
[0017] When the stent is a plastic stent, the substrate pretreatment layer is prepared by the following method: dispersing TiO2 nanoparticles with a particle size of less than 100 nm in a solution to form a TiO2 suspension, and spraying the TiO2 suspension on the surface of the plastic stent to form a rough surface. The solution is selected from one or a combination of two or more of water, ethanol solution, and carbon fluoride.
[0018] Preferably, the solution is carbon fluoride, and the carbon fluoride is selected from one or a combination of two or more of perfluorooctyltrichlorosilane, perfluorooctyltriethoxysilane, perfluorodecyltriethoxysilane, perfluorodecyltrichlorosilane, nonafluorohexyltrimethoxysilane, and tridecafluorooctyltrimethoxysilane.
[0019] In a second aspect, the present invention provides a method for preparing a stent having a super lubricating coating according to the first aspect of the present invention, characterized in that the method comprises the following steps:
[0020] S1: pretreating the surface of the stent substrate to obtain a rough porous surface;
[0021] S2: soaking the scaffold substrate with a rough porous surface in an ethanol solution of carbon fluoride, taking it out and drying it, thereby forming a super hydrophobic layer on the rough porous surface;
[0022] S3: Soaking the material of step S2 in a fluorine-containing lubricating liquid to form a lubricating layer on the super-hydrophobic layer.
[0023] The bracket includes a metal bracket or a plastic bracket.
[0024] When the bracket is a metal bracket, the pretreatment method described in step S1 is: using the metal bracket as the anode and the graphite electrode as the cathode, ionizing in the electrolyte for 6-24 hours, the surface of the metal bracket is oxidized, and the metal oxide is deposited on the surface of the bracket to form a porous anodized surface.
[0025] In a specific embodiment of the present invention, the metal stent is a nickel-titanium alloy metal stent, and the electrolyte is a glycerol ammonium fluoride solution with a volume fraction of 0.5-1.0%.
[0026] In a specific embodiment of the present invention, the metal stent is a nickel-titanium alloy stent, the electrolyte is a 0.5-1.0% volume fraction of glycerol ammonium fluoride solution, 15-30V, oxidation for 2-4h.
[0027] In a specific embodiment of the present invention, the metal stent is a cobalt-chromium alloy stent, which is oxidized in a fluorine-containing electrolyte at a voltage of 2-10V for 0.5-4h.
[0028] In a specific embodiment of the present invention, the metal stent is a magnesium alloy stent, which is oxidized in a fluorine-containing electrolyte at a voltage of 80-140V for 20-50s.
[0029] In a specific embodiment of the present invention, the metal stent is a stainless steel metal stent, and the porous surface is prepared by micro-arc oxidation.
[0030] In a specific embodiment of the present invention, the metal stent is a tantalum alloy metal stent, the electrolyte is an ethanol ammonium fluoride solution with a mass fraction of 1.5-4.0%, and the oxidation is carried out at a voltage of 35-65V for 20-70min.
[0031] In a specific embodiment of the present invention, the metal stent is a titanium alloy metal stent, which is anodized according to the AMS2487 standard processing method.
[0032] In a specific embodiment of the present invention, the substrate pretreatment layer of the nickel-titanium alloy metal bracket is prepared by the following method: the nickel-titanium alloy metal bracket is used as the anode, the graphite electrode is used as the cathode, and a 0.5% volume fraction of propylene glycol ammonium fluoride solution is used as the electrolyte. Anodization is performed for 6-24 hours under 30V, 300mA DC power supply conditions, and the oxidized anode is heat-treated with a peak temperature of 400°C for 6-12 hours and an annealing time of 30 minutes to obtain a porous anodized surface.
[0033] When the stent is a plastic stent, the pretreatment method described in step S1 is: dispersing TiO2 nanoparticles with a particle size of less than 100 nm in a solution to form a TiO2 suspension, and spraying the TiO2 suspension on the surface of the plastic stent to form a rough surface. The solution is selected from one or a combination of water, ethanol solution, and carbon fluoride.
[0034] When the solution is selected from carbon fluoride, it is equivalent to combining steps S1 and S2 in the above preparation method. Specifically, TiO2 nanoparticles with a particle size of less than 100 nm are dispersed in carbon fluoride to form a TiO2 suspension, and the TiO2 suspension is sprayed on the surface of the plastic bracket to form a rough surface and a carbon fluoride layer is prepared at the same time.
[0035] In a third aspect, the present invention provides a use of the stent with a super-lubricating coating as described in the first aspect of the present invention in preparing a supporting material or a prosthesis for dilation of a stenotic cavity in a human body.
[0036] The support material or prosthesis is selected from at least one of a vascular stent, a tracheal stent, a bronchial stent, a urethral stent, an esophageal stent, a laryngeal implant, a biliary stent, a ureteral stent, a stent for the small intestine, and a stent for the large intestine.
[0037] The stent with super lubricating coating of the present invention has the following technical advantages:
[0038] 1) Traditional coatings used for in vivo stents are often difficult to maintain effectiveness during long-term use due to problems such as degradation, wear or poor biocompatibility. The present invention uses FDA-certified biocompatible materials to effectively overcome biocompatibility issues, ensuring that the stent maintains its structural integrity and functional stability for a longer period of time, providing more durable and stable performance, thereby significantly extending the service life of the stent.
[0039] 2) The present invention constructs a porous microstructure on the surface of the stent substrate and then couples fluorinated carbon and perfluorodecalin on the surface to maintain long-term antifouling performance.
[0040] 3) Since perfluorinated compounds repel the adhesion of other molecules at the molecular level, a super-lubricating coating prepared from fluorinated carbon and perfluorodecalin and applied to the surface of the stent can effectively reduce the adhesion of various components and bacteria on the coating surface, reduce the occurrence of stent-related stones and stent-related infections, and can be applied to various common metal and plastic stents in clinical practice, with great clinical value.
[0041] 4) The material used to prepare the stent coating of the present invention is an FDA-certified material, and its biosafety has been verified and has good safety. Secondly, a series of animal experiments have proved that the stent with super-lubricating coating provided by the present invention has long-lasting anti-fouling properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 SEM images of the surface of the nickel-titanium alloy metal stent before and after anodization.
[0043] Figure 2 Determination of water contact angle of superhydrophobic substrate layer.
[0044] Figure 3 Graph showing the anti-bile adhesion effect of super-lubricating coating in vitro.
[0045] Figure 4 Superlubricious coating superlubricity effect diagram.
[0046] Figure 5 The anti-bile adhesion effect of super-lubricating coating in rabbits.
[0047] Figure 6 Graph showing the anti-bacterial adhesion effect of superlubricating coating in vitro. DETAILED DESCRIPTION
[0048] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Example 1 Preparation of a NiTi Alloy Metal Stent with a Super Lubricating Coating
[0050] S1: NiTi alloy metal stent is used as anode, graphite electrode is used as cathode, 0.5% glycerol ammonium fluoride solution is used as electrolyte, and anodization is performed for 2-4 hours under 30V, 300mA DC power supply conditions.
[0051] S2: Heat treatment of the oxidized anode, peak temperature 400℃ for 6-12h, annealing time 30min, to obtain a porous anodized surface
[0052] S3: The obtained porous plate was cleaned 3 times with anhydrous alcohol in an ultrasonic cleaner, and then the surface was blown dry with N2.
[0053] S4: Soak the obtained material in a 0.05 mM perfluorooctyltrichlorosilane ethanol solution for 6 min, remove it and rinse it with anhydrous ethanol three times, each rinsing for 30 s;
[0054] S5: drying the rinsed material at 65°C for 18h;
[0055] S6: The dried material is immersed in 18-fluorodecahydronaphthalene, and a super-lubricating coating is prepared on the surface of the nickel-titanium alloy by relying on the interaction between perfluorinated compounds.
[0056] Example 2 Preparation of a magnesium alloy metal stent with a superlubricating coating
[0057] S1: Take the AZ31B magnesium alloy stent, clean it with anhydrous ethanol in an ultrasonic cleaner for 2-3 times, and then blow dry it with N2.
[0058] S2: Use a magnesium alloy metal support as an anode and graphite as a cathode, and oxidize it in an aqueous solution of 0.5-3.0% ammonium fluoride (common electrolytes are acceptable) at a voltage of 80-140V for 20-50s, then remove it and blow dry it with N2.
[0059] S3: Clean the stent with anhydrous ethanol 2-3 times and blow dry with N2.
[0060] S4: Place the stent in a 1-5% fluorocarbon ethanol solution for 15-30 minutes, then rinse with anhydrous ethanol 2-3 times, 2 minutes each time, and then blow dry with N2.
[0061] S5: Dry the rinsed stent at 60-100° C. for 30-50 min.
[0062] S6: Soak the dried stent in octafluorodecahydronaphthalene.
[0063] Example 3 Preparation of a plastic material stent with a super lubricating coating
[0064] S1: Select TiO2 particles with a diameter less than 100nm, and immerse the TiO2 particles in a 1.0-5.0% carbon fluoride solution. The reaction system is protected by high fluoride, so that the high fluoride forms a protective layer on the surface.
[0065] S2: Wash the plastic bracket three times with anhydrous ethanol and then blow dry with N2.
[0066] S3: Spray the prepared TiO2 suspension onto the surface of a plastic (such as polyethylene, polytetrafluoroethylene, polyurethane, etc.) stent and leave it at room temperature overnight;
[0067] S4: Soaking the material of step S3 in perfluorodecalin to prepare a superlubricating coating on the plastic surface by virtue of the interaction between perfluorinated compounds.
[0068] Effect Example 1: Super-hydrophobic base layer performance test
[0069] Take a nickel-titanium alloy metal sheet, and prepare a coating on the surface of the metal sheet according to the method of Example 1. According to the preparation steps, a nickel-titanium alloy pretreatment layer is obtained through the first step, that is, ionization forms a TiO2 layer on the alloy surface (represented by titanium dioxide in the figure); a coating whose outermost layer is a super-hydrophobic layer is obtained through the first and second steps (represented by super-hydrophobic coating in the figure); a coating whose outermost layer is a lubricating layer is obtained through the first, second and third steps (represented by super-hydrophobic + lubricating coating in the figure); a bare nickel-titanium alloy metal sheet without coating is used as a blank control (represented by nickel-titanium alloy in the figure). The water contact angle of each group of samples is tested with 2 μL of water, as shown in FIG. Figure 2As shown, the water contact angle of the nickel-titanium alloy is about 64°, while the water contact angle of the superhydrophobic substrate is about 167°, which meets the definition of superhydrophobic water contact angle > 150°.
[0070] Effect Example 2 In vitro anti-adhesion performance test
[0071] Take a nickel-titanium alloy metal sheet and prepare a coating on the surface of the metal sheet according to the method of Example 1. The preparation method and grouping of the coating are the same as those of the above-mentioned effect example 1. Soak them in bile for 1 month, during which the bile is regularly replaced, and take out the metal sheet. Figure 3 It can be seen that there is obvious bile mud deposition on the nickel-titanium metal plate, while there is no bile mud adhesion on the surface of the group with superlubricating coating (superhydrophobic + lubricating coating in the figure).
[0072] Effect Example 3 Lubrication Performance Test
[0073] A nickel-titanium alloy sheet was taken and a coating was prepared on the surface of the sheet according to the method of Example 1. A bare nickel-titanium alloy sheet without a coating was taken as a blank control, and a drop of bile was dripped on the top of the sheet, and the time taken for the bile to flow to 1 / 3, 1 / 2 and the bottom of the sheet was recorded. The test results are shown in FIG. Figure 4 As shown, compared with the bare nickel-titanium alloy metal sheet, the surface lubrication performance of the metal sheet with the coating is excellent, and the time taken for bile to flow to the 1 / 3, 1 / 2 and bottom of the metal sheet is significantly less than that of the bare nickel-titanium alloy metal sheet.
[0074] Effect Example 4 In vivo anti-adhesion performance test
[0075] Take nickel-titanium alloy wire, and prepare coating on the surface of metal sheet according to the method of Example 1. The preparation method and grouping of coating are the same as those of effect example 1. Nickel-titanium alloy wire, anodized wire only, wire with super-hydrophobic coating, and wire with super-hydrophobic super-lubricating coating are implanted into rabbit gallbladder respectively. Rabbits are fed normally for 1 month, and then the rabbits are killed and wires are taken out. The results are as follows: Figure 5 As shown: there is blocky bile sludge adhesion on the surface of the nickel-titanium wire, while no obvious adhesion is found on the surface of the super-hydrophobic and super-lubricating coating group. Subsequent confocal scanning quantitatively proves that both the maximum adhesion thickness and the average adhesion thickness of the super-hydrophobic coating group and the super-hydrophobic + lubricating coating group are much lower than those of the nickel-titanium alloy group.
[0076] Effect Example 5 In vitro antibacterial adhesion performance test
[0077] A nickel-titanium alloy stent was taken, and a coating was prepared on the surface of the metal sheet according to the method of Example 1. The preparation method and grouping of the coating were the same as those of the above-mentioned effect example 1. The stent with super-lubricating coating and the nickel-titanium alloy stent were co-cultured in Escherichia coli and Staphylococcus aureus bacterial solution for 1 and 7 days respectively. The stent was taken out, and the surface adherent bacteria were fully transferred to PBS by ultrasonic cleaning machine, and the obtained bacterial solution was diluted and coated on the plate and counted. The results are as follows: Figure 6 It can be seen that the number of bacteria adhering to the surface of the superlubricating coating group (superhydrophobic + lubricating coating in the figure) is significantly reduced compared to the nickel-titanium alloy group.
[0078] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A stent with a super lubricating coating, characterized in that: The stent is composed of a stent substrate and a super-lubricating coating, and the super-lubricating coating is composed of a substrate pretreatment layer, a super-hydrophobic layer and a lubricating layer on the inside and outside; the substrate pretreatment layer is based on the stent substrate, and the stent substrate is pretreated by ionization or nanoparticle loading to prepare a rough porous surface with a large specific surface area, the super-hydrophobic layer material is selected from fluorinated carbon material, and the lubricating layer material is selected from fluorinated lubricating liquid.
2. The stent with super lubricious coating according to claim 1, characterized in that: The stent is a supporting material or a prosthesis used to expand a body cavity, wherein the body cavity includes at least one of a blood vessel, an esophagus, a bile duct, a trachea, a bronchus, a small intestine, a large intestine, a urethra or a ureter.
3. The stent with super lubricious coating according to claim 1, characterized in that: The stent includes a metal stent or a plastic stent; the stent substrate of the metal stent is selected from at least one of nickel-titanium alloy, cobalt-chromium alloy, magnesium alloy, stainless steel, tantalum alloy, and titanium alloy; the stent substrate of the plastic stent is selected from at least one of polyethylene, polyurethane, polytetrafluoroethylene, polypropylene, polyvinylidene fluoride, polyetheretherketone, polylactic acid, and polycaprolactone; When the support is a metal support, the substrate pretreatment layer is prepared by the following method: using the metal support as an anode and the graphite electrode as a cathode, ionizing in an electrolyte for 6-24 hours, the surface of the metal support is oxidized, and the metal oxide is deposited on the surface of the support to form a porous anodized surface; When the stent is a plastic stent, the substrate pretreatment layer is prepared by the following method: dispersing TiO2 nanoparticles with a particle size of less than 100 nm in a solution to form a TiO2 suspension, and spraying the TiO2 suspension on the surface of the plastic stent to form a rough surface.
4. The stent with super lubricious coating according to claim 1, characterized in that: The fluorinated carbon material is selected from one or a combination of two or more of perfluorooctyltrichlorosilane, perfluorodecyltriethoxysilane, perfluorodecyltrichlorosilane, nonafluorohexyltrimethoxysilane, and tridecafluorooctyltrimethoxysilane; the fluorinated lubricant is selected from perfluorodecalin, fluorinated polyether, or fluorinated alkane amine.
5. The stent with super lubricious coating according to claim 1, characterized in that: The super hydrophobic layer material is selected from perfluorooctyltrichlorosilane, and the lubricating layer material is selected from perfluorodecalin.
6. A method for preparing a stent having a super lubricating coating according to any one of claims 1 to 5, the method comprising the following steps: S1: pretreating the surface of the stent substrate to obtain a rough porous surface; S2: soaking the scaffold substrate with a rough porous surface in an ethanol solution of carbon fluoride, taking it out and drying it, thereby forming a super hydrophobic layer on the rough porous surface; S3: Soak the material of step S2 in a fluorine-containing lubricating liquid, remove and dry, and form a super lubricating layer on the super hydrophobic layer.
7. The preparation method according to claim 6, characterized in that: The stent comprises a metal stent or a plastic stent; When the bracket is a metal bracket, the pretreatment method described in step S1 is: using the metal bracket as an anode and the graphite electrode as a cathode, ionizing in an electrolyte for 6-24 hours, the surface of the metal bracket is oxidized, and the metal oxide is deposited on the surface of the bracket to form a porous anodized surface; When the stent is a plastic stent, the pretreatment method described in step S1 is: dispersing TiO2 nanoparticles with a particle size of less than 100 nm in a solution to form a TiO2 suspension, and spraying the TiO2 suspension on the surface of the plastic stent to form a rough surface; the solution is selected from one or a combination of two or more of water, ethanol solution, and carbon fluoride.
8. The preparation method according to claim 7, characterized in that: The metal bracket is a nickel-titanium alloy bracket, the electrolyte is a propylene glycol ammonium fluoride solution with a volume fraction of 0.5-1.0%, 15-30V, and oxidation for 2-4h; the metal bracket is a cobalt-chromium alloy bracket, in a fluorine-containing electrolyte, oxidation is performed at a voltage of 2-10V for 0.5-4h; the metal bracket is a magnesium alloy bracket, in a fluorine-containing electrolyte, oxidation is performed at a voltage of 80-140V for 20-50s; the metal bracket is a stainless steel metal bracket, and a porous surface is prepared by micro-arc oxidation; the metal bracket is a tantalum alloy metal bracket, the electrolyte is an ethanol ammonium fluoride solution with a mass fraction of 1.5-4.0%, and oxidation is performed at a voltage of 35-65V for 20-70min; the metal bracket is a titanium alloy metal bracket, and anodization is performed according to the AMS2487 standard treatment method.
9. Use of the stent with superlubricating coating according to any one of claims 1 to 5 in preparing a supporting material or a prosthesis for dilation of stenosis of a human cavity.
10. The use according to claim 9, characterized in that The support material or prosthesis is selected from at least one of a vascular stent, a tracheal stent, a bronchial stent, a urethral stent, an esophageal stent, a laryngeal implant, a biliary stent, a ureteral stent, a stent for the small intestine, and a stent for the large intestine.
Citation Information
Cited By
Coating precursor, method of preparation and gel plastic alloy superlubricant coating
CN122772449A